Penser l’imprévisibilité dans les dispositifs des formations ouvertes et à distance - Melpomeni Papadopoulou (Éducation et Socialisation)
The arrival of new technologies in the field of adult education has a significant influence on teaching and learning practices. Our contribution questions the place of unpredictability, intrinsic to adult training situations, in the framework of ODL. How can we think about the relationship between technical constraints and freedom of action, between content didactics and life hazards, and finally, between programming and improvisation? The interdependent relationship between professional gestures on the one hand and flexible technical environments on the other hand is pointed out in order to take into account the unpredictability of teaching and learning situations.